Textual Research on the Gongxu Edition of Guoyu during the Song Dynasty - Qu, Jingyi (Beijing Normal University Publishing Group & Anhui University Press, 2017)
The edition problem of Guoyu 國語 is the basis of the study of the Guoyu’s, but the correlational research is blank. This paper explored some important problems about the Gongxu 公序 edition during the Song Dynasty, especially the true situation about three Song printed editions which were collected by libraries across the Tai Wan Straits. It concluded that the Gongxu edition was firstly engraved by the Guozijian during Emperor Yingzong’s reign (1063-1067) period in the Northern Song, and that they were twice carved during reigns of Emperor Gaozong (1127-1162) and Xiaozong (1162-1189) in the Southern Song.